Appendicitis presenting as LUQ pain in an anatomically normal patient: a case study - Ferris, Baillie W. C. (International Surgery Journal, 2018)
Appendicitis typically presents with right sided pain, but some patients present with left sided symptoms. This is most commonly due to anatomical abnormalities such as intestinal malrotation or Situs Inversus. In this case study I present a case where an anatomically normal patient presented with Left Upper Quadrant (LUQ) pain. I hypothesize that the reason for this is incorrect interpretation of visceral nociceptive afferents by the Central Nervous System (CNS). I review the literature in regard to the “visceral homunculus.” I also review the literature with regards to left sided ab-domical pain and Appendicitis. This case highlights the importance of considering Appendicitis in LUQ pain.